Ignorance and liberty - Infantino, Lorenzo, 1948- (Routledge studies in social and political thought ;, 2003)
Free social cooperation helps to mobilize our knowledge and develop methods of discovery in which we can explore the unknown, correct errors, accept criticism, aid our rationality and further political and economic development.